Challenging the prison-industrial complex: activism, arts, and educational alternatives - Hartnett, Stephen John (Univ. of Illinois Press, 2011)
Building an abolition democracy; or, the fight against public fear, private benefits, and prison expansion / Erica R. Meiners -- Poem. Another day in the Champaign County Jail / Dennis Mansker -- Militarizing the police : Officer Jon Burge, torture, and war in the "urban jungle" / Julilly Kohler-Hausmann -- Poem. Gotta be careful where ya plant ya feet / Marvin Mays -- Killing democracy; or, how the drug war drives the prison-industrial complex / Daniel Mark Larson -- Poem. Another day / Erika Baro -- Teaching you to love fear : television news and racial stereotypes in a punishing democracy / Travis L. Dixon -- Poem. In search of salvation / William T. Smith -- Diagnosing the schools-to-prisons pipeline : maximum security, minimum learning / Rose Braz and Myesha Williams -- A piece of the reply : the Prison Creative Arts Project and practicing resistance / Buzz Alexander -- Poem. The poet's corner / George Hall -- Each one reach one : playwriting and community activism as redemption and prevention / Robin Sohnen -- Poem. Devil talks / Robert "Chicago" McCollum -- Fostering cultures of achievement in urban schools : how to work toward the abolition of the schools-to-prisons pipeline / Garrett Albert Duncan -- Poem. January 3, 2009 / Nicole Monahan -- Humanizing education behind bars : Shakespeare and the theater of empowerment / Jonathan Shailor -- Poem. Anger / Kenneth Sean Kelly -- Breaking down the walls : inside-out learning and the pedagogy of transformation / Lori Pompa